ANALISIS KEPUASAN SISWA, WALI MURID, DAN GURU TERHADAP PEMBELAJARAN PROJEK KURIKULUM MERDEKA KELAS 4 SEKOLAH DASAR - Nurul Khasanah; Nataria Wahyuning Subayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
The trial implementation of the learning project for strengthening the Pancasila profile has been carried out in various elementary schools in Indonesia. Therefore, it is necessary to analyze the satisfaction of the learning. This study aims to analyze the level of satisfaction, both for teachers, students, and guardians of students towards learning the Pancasila student profile strengthening project in the independent learning curriculum in grade 4 SD Muhammadiyah 2 GKB Gresik. This type of research is descriptive research using a survey approach method. The variable in this study is satisfaction with learning the independent learning curriculum project. The research was conducted in the 4th grade of SD Muhammadiyah 2 GKB on October 21, 2022. A total of 4 teachers, 26 students, and 26 guardians were selected as research samples by total sampling. Data collection was carried out using a satisfaction index questionnaire. Importance-performance analysis by John A. Martila and John C. James The results of this study indicate that the average student (100.14%), parents (99.96%) and teachers (133 ,42%) satisfied with the learning of the Pancasila profile education strengthening project at the elementary school level at SD Muhammadiyah 2 GKB Gresik. The results of this study are expected to be an evaluation material for curriculum development in schools.